2017
DOI: 10.1177/1470320316687197
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme inhibitors attenuate propofol-induced pro-oxidative and antifibrinolytic effect in human endothelial cells

Abstract: Introduction:The aim of this study was to investigate the effects of plasma and tissue angiotensin-converting enzyme inhibitors (ACE-Is) against propofol-induced endothelial dysfunction and to elucidate the involved mechanisms in vitro.Materials and methods:We examined the effects of propofol (50 μM), quinaprilat and enalaprilat (10−5 M) on fibrinolysis (t-PA, PAI-1, TAFI antigen levels), oxidative stress parameters (H2O2 and MDA antigen levels and SOD and NADPH oxidase mRNA levels) and nitric oxide bioavailab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Next, we investigated the effect of the HC diet-feeding on serum and liver levels of the anti-coagulation and antiplatelet molecules, sulfatides, which are also regulated by PPARα, in WT and Ppara -null mice (Marx et al 2001; Kimura et al 2012; Masuda et al 2012; Kanbe et al 2014; Gonsalves et al 2015; Wojewodzka-Zelezniakowicz et al 2017). Liver and serum levels of sulfatides were similar between WT and Ppara -null mice fed with the control diet, and these levels became markedly lower in mice of either genotype fed the HC diet.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, we investigated the effect of the HC diet-feeding on serum and liver levels of the anti-coagulation and antiplatelet molecules, sulfatides, which are also regulated by PPARα, in WT and Ppara -null mice (Marx et al 2001; Kimura et al 2012; Masuda et al 2012; Kanbe et al 2014; Gonsalves et al 2015; Wojewodzka-Zelezniakowicz et al 2017). Liver and serum levels of sulfatides were similar between WT and Ppara -null mice fed with the control diet, and these levels became markedly lower in mice of either genotype fed the HC diet.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that the HC diet increases oxidative stress (Naziroglu et al 2014). Indeed, levels of the thrombotic factors TF, PAI-1, and sulfatides are influenced by oxidative stress (Marx et al 2001; Kimura et al 2012; Masuda et al 2012; Kanbe et al 2014; Gonsalves et al 2015; Wojewodzka-Zelezniakowicz et al 2017), and that PPARα exerts anti-oxidative effects (Kamijo et al 2007). Therefore, we investigated the effects of feeding the HC diet on hepatic oxidative stress and the related factors in WT and Ppara -null mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After 2 h of incubation, cell supernatants were collected, and TF, t-PA, PAI-I, NO 2 /NO 3 , H 2 O 2 , and MDA levels were measured with commercially available kits. Endothelial nitric oxide synthase (eNOS) expression at the mRNA level was determined by quantitative real-time PCR as previously described [ 9 , 34 ]. The following PCR primers were designed: 5′-CATCGGCGTGCTGCGGGATCAG-3′ and 5′-GGGCTGTTGGTGTCTGAGCCGG-3′, which were specific for the mRNAs of eNOS.…”
Section: Methodsmentioning
confidence: 99%
“…Enalapril 1) Enhances GSH [118] 2) Scavenges ROS [119] Captopril 1) Enhances GSH [118] 2) Protects EC from H 2 O 2 through AKT/mTOR pathway [120] 3) Suppresses NOX expression [121] 4) Scavenges ROS [119] Quinaprilat 1) Decreases H 2 O 2 and MDA induced by propofol [122] Enalaprilat 1) Decreases H 2 O 2 induced by propofol [122] 2) Increases SOD activity and reduces the thiobarbituric acid reactive substances level [144] Lisinopril 1) Reduces Superoxide and hydroxyl radical in diabetic myocardium [145] 2) Reduces serum markers of oxidative stress [146] Perindopril 1) Increases eNOS expression and activity [147] 2) Increases NO [147] Angiotensin II receptor blockers Irbesartan 1) Reduces superoxide and p22phox [126,148] 2) Increases NO bioavailability [148] 3) Increases GSH and SOD activity [149] Olmesartan 1) Reduces as 8-epi-prostaglandin F2α (8-epi-PGF2α) and 8-hydroxydeoxyguanosine (OHdG) [125] 2) Reduces ROS production [150] 3) Enhances NO release [151] Azilsartan 1) Improves eNOS activity and reduces NOX2 and NOX4 expression [127] 2) Restores uncoupled eNOS [127] 3) Inhibits NOX2 and NOX4 [127] Valsartan 1) Reduces 8-epi-PGF2α and OHdG [125] 2) Reduces ROS generated by polymorphonuclear cells and mononuclear cells [128,152] 3) Promotes NO synthesis [153] Calcium channel blockers Amlodipine 1) Enhances NO formation and increases NO bioavailability [130] 2) Promotes the unclamping of eNOS from caveolin to potentiate NO production [154] 3) Reduces O 2 − and ONOO − production [155] Benidipine 1) Inhibits ROS production [131] 2) Decreases oxidative stress in polymorphonuclear cells [156] Lacidipine 1) Reduces the ox-LDL induced ROS [129a]…”
Section: Ace Inhibitorsmentioning
confidence: 99%